2022
DOI: 10.3390/jcm11185448
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Levels of Calprotectin and Soluble Receptor for Advanced Glycation End Products with Abdominal Aortic Aneurysm Diameter: A Preliminary Clinical Trial

Abstract: An abdominal aortic aneurysm (AAA) is a dilatation of the abdominal aorta greater than 50% of the diameter of a healthy aorta. Previous experimental studies confirm the effect of calprotectin (CAL) on the onset of arterial pathology. It has been suggested that low levels of soluble receptors for advanced glycation end products (RAGEs) increase levels of cytokines that lead to the inhibition of matrix metalloproteinases (MMPs), affecting AAA formation. This study aimed to analyze the correlation of levels of RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…15 They also found differences in the levels of soluble receptor for advanced glycation end products (RAGE) between the two groups, 16 but were unable to establish a correlation between both markers (calprotectin or RAGE) and aortic diameter, probably due to limited sample size. 17 Liu et al 18 also showed increased levels of calprotectin in AAA serum samples. Our results corroborate those of Hauzer et al and Liu et al, and all together appear to highlight the role of calprotectin as a feasible AAA biomarker.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…15 They also found differences in the levels of soluble receptor for advanced glycation end products (RAGE) between the two groups, 16 but were unable to establish a correlation between both markers (calprotectin or RAGE) and aortic diameter, probably due to limited sample size. 17 Liu et al 18 also showed increased levels of calprotectin in AAA serum samples. Our results corroborate those of Hauzer et al and Liu et al, and all together appear to highlight the role of calprotectin as a feasible AAA biomarker.…”
Section: Discussionmentioning
confidence: 94%
“…15 They also found differences in the levels of soluble receptor for advanced glycation end products (RAGE) between the two groups, 16 but were unable to establish a correlation between both markers (calprotectin or RAGE) and aortic diameter, probably due to limited sample size. 17 In contrast, our control group comprised healthy volunteers and carotid endarterectomy patients with severe atherosclerosis, who were analyzed separately to determine whether calprotectin would be able to differentiate AAA from other vascular diseases. Interestingly, calprotectin levels were higher in patients with AAA than in the HV and CE groups, whereas HV and CE showed similar calprotectin levels, highlighting its specificity as an AAA biomarker in cardiovascular context.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of the cross-linking AGE pentosidine have been negatively correlated with aortic diameter [ 40 ], suggesting a protective effect against aortic dilatation. On the other hand, increased SAF of AGE has been reported in patients with AAA compared with controls independently of the presence of concomitant atherosclerosis [ 41 ], and levels of the soluble receptor for AGE have been correlated to AAA size [ 42 ]. Blocking of this receptor has even been evaluated in animal models and proposed as a potential future treatment of AAA [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AAA also display an increased level of calprotectin in comparison to patients with a healthy aorta. That level decreases significantly after the removal of AAA [11,12].…”
Section: Pathogenesis Of Aaa Formationmentioning
confidence: 93%